Investigation of the Usability of Serum Phospholipase A2, Neutrophil/Lymphocyte Ratio, Red Cell Distribution Width and Mean Platelet Volume Levels in the Grading of Scorpion Envenomation - İrfan Aydın; Mehmet Kaan Poyraz; Kasım Turgut; Abdullah Algın; Nurettin Aktaş (Eurasian Journal of Emergency Medicine, 2022)

(untitled)
Aim:This study aimed to compare the serum phospholipase A2, neutrophil/lymphocyte ratio (NLR), red cell distribution width (RDW), and mean platelet volume (MPV) levels of patients who presented to our emergency department due to scorpion stings and to determine a laboratory parameter that could assist in clinical grading.Materials and Methods:Sixty-three patients presenting to the emergency department due to scorpion stings and 33 volunteers presenting for other reasons between May and October 2018 were included in the study. The serum phospholipase A2, NRL, RDW and MPV levels of the patients were determined and compared with the control group.Results:In the evaluation performed in the patient group, the mean serum leukocyte and serum lymphocytes were higher and the RDW mean was statistically significantly lower compared to the control group, (p=0.001, 0.003, and 0.004, respectively). There was no significant difference between the patient and control groups in terms of the serum MPV, platelet and serum phospholipase levels (p>0.05). When the patients’ serum MPV values were compared according to their clinical grade, a statistically significant correlation was found (rho: - 0.432, p<0.001).Conclusion:In scorpion stings, as the clinical grade progresses, the MPV rate decreases. Therefore, the MPV level can be used as an auxiliary parameter to show the severity of scorpion stings.